Words, dictionaries and sociology: The impact of coroneologisms. - Lan Li (Lexicography, 2021)
The COVID-19 pandemic has lasted for more than one year with a devastating effect on the whole world. This paper illustrates word-formation approaches and semantic webs of COVID-19 vocabulary that is said to number more than 1000 new words; it also discusses significant events that created 'coroneologisms'. In this connection, the paper takes a corpus-based approach towards content analysis and semantic relationship networks by studying the massive data associated with the pandemic: news reports, government documents, international policies, science papers, social media posts and others. Three online mega-corpora and self-collected data were analysed from the lexicological perspective, including affixation, compounding, blending, acronyms, and word meanings associated with common words. The paper also reifies the efforts of lexicographers, especially those of the Oxford English Dictionary (OED), in recording this unprecedented catastrophe in human history. In using the semantic web, aspects of language are shown to have developed during this period. The broader purpose is to ascertain how language, as a social enterprise, has changed in tandem with empirically ascertainable social, political and scientific changes during the pandemic. The underlying belief advanced here is that the more indepth study we conduct into COVID-19 (related) vocabulary, the more we can understand the pandemic and document its history.